Airway Management of Two Patients with Penetrating Neck Trauma - Bhattacharya, P (Medknow Publications, 2009)
SUMMARY: Direct trauma to the airway is a rare injury which can lead to disastrous consequences due to compounding effect of bleeding, aspiration of blood, airway obstruction and severe sympathetic stimulation. Here we are presenting two cases of open tracheal injury in two adult males following assault with sharp weapon. Two different techniques of securing the airways were employed depending upon the severity and urgency of the situation. In the first case, orotracheal intubation helped the surgeon to repair airway around the endotracheal tube whereas in the second patient this stenting effect was absent as he was intubated through the distal cut-end of trachea in the face of airway emergency.